The Influence of Exchange Rate, Interest Rates and Company Size on Capital Structure on The Indonesian Stock Exchange - Mardiputra, Ilham Muhammad; Haliliintar, Muhammad; Syaiful, Syaiful (Dinasti International Journal of Digital Business Management, 2024)
This research is quantitative research. The aim of this research is to find out whether The Influence Of Exchange Rate, Interest Rates And Company Size On Capital Structure On The Indonesian Stock Exchange on the Indonesian Stock Exchange. 22 corporate bonds were obtained from 11 issuing banking sector companies as samples. The CR variable has a positive but insignificant effect on the DER ratio of banking sector companies that issue bonds and are listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The SIZE variable has a positive and significant effect on the DER of banking sector companies that issue bonds and are listed on the Indonesia Stock Exchange. FOREX variable has a negative and significant effect on the DER of banking sector companies that issue bonds and are listed on the Indonesia Stock Exchange. All independent variables consisting of; Company Size (SIZE), Exchange Rate (FOREX), and Interest Rate (IR) together significantly affect the Capital Structure (DER) of banking sector companies that issue bonds and are listed on the Indonesia Stock Exchange